2, 2′-Bipyridyl formation from 2-arylpyridines through bimetallic diyttrium intermediate1. Issue 10 (14th October 2015) - Shibata, Yu; Nagae, Haruki; Sumiya, Shiki; Rochat, Raphaël; Tsurugi, Hayato; Mashima, Kazushi
<x xml:space="preserve">Abstract</x> Formation of dianionic 2, 2′-bipyridyl-bridged dinuclear yttrium complexes proceeded upon treatment of (ArNCH2CH2NAr)Y(CH2SiMe3)(THF)2 with 2-arylpyridine, in which mononuclear (2-pyridylphenyl)yttrium complexes were detected as key intermediates.